HUBUNGAN PENGETAHUAN DAN PERAN KADER POSYANDU TERHADAP PEMBERIAN IMUNISASI BOSTER DPTHBHIB DAN CAMPAK PADA BATITA DI WILAYAH KERJA PUSKESMAS BATU AJI KELURAHAN BULIANG KECAMATAN BATU AJI KOTA BATAM TAHUN 2017 - Damanik, Donna Kristiana; Susanti, Rini (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
The success improvement on thehealth aspects is prominently directed by attempts to reduce the mortality rate of both infants and toddlers. One of the efforts is routinely give the complete vaccinations for them. This study aims to examine the correlation of the knowledge levels and role of health personnel of the Integrated Heath Post to provide pentabioand measles immunizationsfor toddlers particularly the ones under three-year old in Buliang Health Centre of BatuAji. The research design used in this study was a descriptive analytic design with 21 respondents chosen through total sampling method. The data was analyzed by chi square statistical test at significance level of 95%. The results show that 17 respondents have good knowledgeand able to implement their knowledge on vaccinations well. From 17 respondents whom actively engaged in vaccination process, 13 of them are able to perform the pentabio and measles vaccinations well. Besides, from the chi square test, it is obtained p-value > 0.05, thus, it can be concluded that there is no significant correlation of the knowledge levels and role of health personnel of the Integrated Heath Post to provide pentabioand measles vaccinationsfor under three-year toddlers. Finally, it is expected that both the health personnel of the integrated health post as well as the civil society to actively take a part in increasing the health quality of the children through giving complete and proper vaccinations for them.